Fecal pollution source tracking at a marine bathing beach: A case study of Beihai Silver Beach - Hongxia Ming; Ziqi Chen; Tingting Shi; Zhongzhi Chen; Wenjing Pan; Jiannan Lin; Jie Su; Jingfeng Fan (Regional Studies in Marine Science, 2026)

A multi-agent system for neighborhood-scale carbon simulation: Integrating intelligent multi-source sensing with interaction-driven modeling - Ao Sun; Xiucheng Zhai; Lefan Pian; Lu Li; Shuyuan Jia; Jingfeng Yuan; Shu Su (Sustainable Cities and Society, 2026)

Environmental DNA reveals shift in phytoplankton community driven by sewage-derived eutrophication in coastal waters - Jie Su; Xuexin Wu; Tingting Shi; Shanshan Dong; Daoyang Shi; Hanjun Chen; Hongxia Ming; Jingfeng Fan (Marine Environmental Research, 2026)

Assessment of spatial and temporal variability in fecal contamination patterns within urbanized bay shellfish growing area utilizing community-based microbial source tracking approaches - Jiannan Lin; Hongxia Ming; Dongwei Li; Jiajie Li; Zhongzhi Chen; Ziqi Chen; Tingting Shi; Jie Su; Jingfeng Fan (Environmental Monitoring and Assessment, 2025)

Interactive and dynamic insights into environmental impacts of a neighborhood: A tight coupling of multi-agent system and dynamic life cycle assessment - Shu Su; Jingyi Ju; Jingfeng Yuan; Yuan Chang; Qian Li (Environmental Impact Assessment Review, 2025)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Spinach leaf disease identification based on deep learning techniques - Laixiang Xu; Jingfeng Su; Bei Li; Yongfeng Fan; Junmin Zhao (Plant Biotechnology Reports, 2024)

An automatic tracking method for fruit abscission of litchi using convolutional networks - Tong Huang; Jingfeng Guo; Long Yu; Houbin Chen; Zuanxian Su; Yueju Xue (Computers and Electronics in Agriculture, 2024)

Promoting the denitrification process by heavy metals in Liaohe Estuary sediment - Ming Hongxia; Zan Shuaijun; Liu Jiwen; Su Jie; Ren Kaijia; Lin Jiannan; Chen Quanrui; Shi Yinyin; Shi Tingting; Fan Jingfeng (Marine Pollution Bulletin, 2024)

Identification and functional characterization of annexin A2 in half-smooth tongue sole (Cynoglossus semilaevis) - Guowei Han; Yufeng Su; Qing Mao; Zhuoran Han; Jingfeng Sun (Fish & Shellfish Immunology, 2024)

Dryland evapotranspiration from remote sensing solar-induced chlorophyll fluorescence: Constraining an optimal stomatal model within a two-source energy balance model - Jingyi Bu; Guojing Gan; Jiahao Chen; Yanxin Su; Mengjia Yuan; Yanchun Gao; Francisco Domingo; Ana López-Ballesteros; Mirco Migliavacca; Tarek S. El-Madany; Pierre Gentine; Jingfeng Xiao; et al. (Remote Sensing of Environment, 2024)

Long-term response of the microbial community to the degradation of DOC released from Undaria pinnatifida - Yuyang Xie; Jie Su; Kuishuang Shao; Tian Hu; Hongxia Ming; Tingting Shi; Wenjing Wang; Jingfeng Fan (Marine Environmental Research, 2024)

Prevalence, antibiotic and heavy metal resistance of Vibrio spp. isolated from the clam Meretrix meretrix at different ages in Geligang, Liaohe estuary in China - Jie Su; Yingxue Zhang; Tian Hu; Hongxia Ming; Yuyang Xie; Yuan Jin; Tingting Shi; Jingfeng Fan (Frontiers in Marine Science, 2022)
Vibrio as one of the main pathogens of shellfish diseases can cause serious human seafoodborne gastroenteritis and even death. In this study, we analyzed the bacterial communities from the clam, and compared the resistance phenotypes and genotypes of Vibrio spp. from Meretrix meretrix at different growth stages. High-throughput sequencing analysis revealed the predominance of Proteobacteria (50%) in the bacterial community and Vibrio was one of the dominant genera in the clam hepatopancreas in the summer. Vibrio abundance in Meretrix meretrix positively correlated with the water temperature (p<0.05). A total of 73 Vibrio isolates from Meretrix meretrix were classified into 19 species and the dominant strains included V. mediterranei (19%) and V. harveyi (11%), V. algolyticus (10%), and V. parahaemolyticus (8%). The species and abundance of Vibrio spp. were the highest in the 3-year-old of Meretrix meretrix compared with clams of other ages in the summer. Among the 73 isolates, 68 Vibrio strains were resistant to other 15 antibiotics except for sulfamethoxazole-trimethoprim with 57 resistant phenotypes. The most prevalent resistance was toward clindamycin (76%), followed by amikacin (63%), ampicillin (62%), rifampicin (62%), vancomycin (57%), and amoxicillin (50%). The ARI values of Vibrio spp. in different ages ranged from 0.13 to 0.18, and ARI values of 3-year-old (ARI=0.18) clams are higher than that of other ages clam. Approximately 72% of the resistant isolates showed multidrug-resistant phenotypes with maximum resistance to 15 antibiotics. Tolerance to heavy metals including Cd, Zn, and Cu was detected in the majority of antibiotic resistant isolates. In addition to the co-resistance to the same class of antibiotics, resistance to cephalosporin (CFP, CEP, CZ) were significantly correlated with penicillins (AMP, AMC) ( p < 0.01), tetracycline ( p < 0.001), sulfanilamide (SXT) ( p < 0.01) and quinolone (CIP) ( p < 0.01). The heavy metal resistance genes copB and nccA were significantly correlated with the clindamycin resistance phenotype ( p <0.01). This study revealed that the habitat of Meretrix meretrix is in low exposure to antibiotics, and a link between heavy metal resistance genes and antibiotic resistance.

Soil moisture regulates warming responses of autumn photosynthetic transition dates in subtropical forests - Yongshuo H. Fu; Xinxi Li; Shouzhi Chen; Zhaofei Wu; Jianrong Su; Xing Li; Shuaifeng Li; Jing Zhang; Jing Tang; Jingfeng Xiao (Global Change Biology, 2022)
Autumn phenology plays a key role in regulating the terrestrial carbon and water balance and their feedbacks to the climate. However, the mechanisms underlying autumn phenology are still poorly understood, especially in subtropical forests. In this study, we extracted the autumn photosynthetic transition dates (APTD) in subtropical China over the period 2003–2017 based on a global, fine‐resolution solar‐induced chlorophyll fluorescence (SIF) dataset (GOSIF) using four fitting methods, and then explored the temporal–spatial variations of APTD and its underlying mechanisms using partial correlation analysis and machine learning methods. We further predicted the APTD shifts under future climate warming conditions by applying process‐based and machine learning‐based models. We found that the APTD was significantly delayed, with an average rate of 7.7 days per decade, in subtropical China during 2003–2017. Both partial correlation analysis and machine learning methods revealed that soil moisture was the primary driver responsible for the APTD changes in southern subtropical monsoon evergreen forest (SEF) and middle subtropical evergreen forest (MEF), whereas solar radiation controlled the APTD variations in the northern evergreen‐broadleaf deciduous mixed forest (NMF). Combining the effects of temperature, soil moisture and radiation, we found a significantly delayed trend in APTD during the 2030–2100 period, but the trend amplitude (0.8 days per decade) was much weaker than that over 2003–2017. In addition, we found that machine learning methods outperformed process‐based models in projecting APTD. Our findings generate from different methods highlight that soil moisture is one of the key players in determining autumn photosynthetic phenological processes in subtropical forests. To comprehensively understand autumn phenological processes, in‐situ manipulative experiments are urgently needed to quantify the contributions of different environmental and physiological factors in regulating plants' response to ongoing climate change.

Monitoring and evaluation of antibiotic resistance genes in three rivers in northeast China - Chen Zhao; Chenyu Li; Xiaoming Wang; Zhuosong Cao; Chao Gao; Sicong Su; Bin Xue; Shang Wang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Environmental Science and Pollution Research, 2022)

Comprehensive evaluation and analysis of the salinity stress response mechanisms based on transcriptome and metabolome of Staphylococcus aureus - Ying Feng; Dizhou Gu; Ziyan Wang; Chenyang Lu; Jingfeng Fan; Jun Zhou; Rixin Wang; Xiurong Su (Archives of Microbiology, 2022)

Assessment models and dynamic variables for dynamic life cycle assessment of buildings: a review - Shu Su; Huan Zhang; Jian Zuo; Xiaodong Li; Jingfeng Yuan (Environmental Science and Pollution Research, 2021)

Spatial distribution characteristics of bacterial community structure and gene abundance in sediments of the Bohai Sea - Quanrui Chen; Jingfeng Fan; Jie Su; Hongxia Ming; Zhihao Sun; Mengfei Li; Xiaohui Zhao; Yantao Wang; Yingxue Zhang; Huizhen Zhang; Yuan Jin; Xiaowan Ma; et al. (Acta Oceanologica Sinica, 2020)

Spatial Abundance, Diversity, and Activity of Ammonia-Oxidizing Bacteria in Coastal Sediments of the Liaohe Estuary - Yongkai Chang; Jingfeng Fan; Jie Su; Hongxia Ming; Wen Zhao; Yan Shi; Fengyun Ji; Limei Guo; Shuaijun Zan; Bochao Li; Hao Guo; Daoming Guan (Current Microbiology, 2017)